Tree Diversity of Gandhinagar City, Gujarat, India - Gadani, Maulik (Indian Forester, 2011)
In the present paper details of tree species raised in various parts of the Gandhinagar city are given. A total of 55 families of tree species were recorded with 146 genera and 219 species. Fabaceae (leguminosae) is the maximum planted family. Apart from improvement of the environment, trees are planted on road sides for beautifying the streets. They also served the purpose of medication, fuel source, etc. In view of the pressure of rapid urbanization, there is a need of conservation ofthis rich diversity.